Variable Effects of Dispersal on Productivity of Bacterial Communities Due to Changes in Functional Trait Composition - Severin, Ina (Public Library of Science, 2013)
Previous studies have shown variable relationships between dispersal rate and ecosystem functioning, but the reasons for and mechanisms behind variable dispersal rate – functioning patterns are currently unknown. In this study we used six bacterial lake water communities in a laboratory experiment in order to investigate how dispersal among communities influences community productivity by evaluating three different mechanisms: 1) changes in taxonomic diversity, 2) changes in phylogenetic diversity or 3) changes in the composition of functional traits. The experiment was conducted in two phases; (A) a dialysis bag experiment where the dispersal rate among six communities was manipulated and the subsequent change in bacterial diversity and growth rate was recorded, and (B) a regrowth experiment where we manipulated available resources to study how well a taxon grows on certain organic carbon resources, i.e. their functional traits. From experiment (B) we could thus estimate changes in functional traits in communities in experiment (A). Bacterial production was affected by dispersal, but not consistently among lakes. Neither change in taxonomic or phylogenetic diversity with dispersal could explain the observed dispersal – productivity relationships. Instead, changes in trait composition with dispersal, especially the communities’ ability to use p-coumaric acid, an aromatic compound, could explain the observed dispersal – productivity relationships. Changes in this trait caused by dispersal seemed especially important for bacterial productivity in waters with a high aromaticity of the organic matter pool. We conclude that the effect of dispersal on bacterial communities can affect ecosystem functioning in different ways, through changes in functional key-traits which are important for the local environment.